2020
DOI: 10.1108/jeas-11-2019-0127
|View full text |Cite
|
Sign up to set email alerts
|

Innovation, institutions and economic growth in sub-Saharan Africa – an IV estimation of a panel threshold model

Abstract: PurposeThe significant impact of innovation in stimulating economic growth cannot be overemphasized, more importantly from policy perspective. For this reason, the relationship between innovation and economic growth in developing economies such as the ones in Africa has remained topical. Yet, innovation as a concept is multi-dimensional and cannot be measured by just one single variable. With hindsight of the traditional measures of innovation in literature, we augment it with the number of scientific journals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 59 publications
(84 reference statements)
0
11
0
Order By: Relevance
“…Moore and Schatz (2017) indicated that overestimation refers to the tendency of market players to overestimate their own skills, their level of success and the degree of control. Odean (1998) and Daniel et al (1998) postulated that economic agents overestimate their skills, abilities, knowledge and beliefs in assessing themselves, and as a result, they become overconfident (Forson et al, 2021). Cwynar et al (2020) indicated that such unending belief in one's knowledge and skills lead to erroneous results.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…Moore and Schatz (2017) indicated that overestimation refers to the tendency of market players to overestimate their own skills, their level of success and the degree of control. Odean (1998) and Daniel et al (1998) postulated that economic agents overestimate their skills, abilities, knowledge and beliefs in assessing themselves, and as a result, they become overconfident (Forson et al, 2021). Cwynar et al (2020) indicated that such unending belief in one's knowledge and skills lead to erroneous results.…”
Section: Theoretical Foundationsmentioning
confidence: 99%
“…The head teacher or director of education as the Chief Executive needs to appreciate and recognize that results can be obtained through people. In today's world, organizations are concerned with what should be done to achieve sustained high level of performance through people who are innovative thinkers [4,17,41]. These include paying more attention to how individuals can best be motivated and provision of an atmosphere that helps individuals to deliver on their mandates in accordance with the expectations of management [25].…”
Section: Introductionmentioning
confidence: 99%
“…The outcome of the current study expands to debate to imply that the advantages of complementing offline sales with online sales could equally be reaped by domestic enterprises irrespective of size. The observation that innovation into online sales could improve the performance of SMEs are well documented [7,8,26]. Moreno et al [20] earlier observed in Belgium that online activities are predominant in large enterprises as compared to SMEs and accordingly observed that online activities have limited impact on the performance of SMEs but significantly influence the performance of large enterprises positively (see Peng et al, [21]).…”
Section: Moderating and Mediating Effects Of Enterprise Ownership And...mentioning
confidence: 96%
“…The outcome of the current study expands the discourse on this matter to imply that the advantages of complementing offline sales with online sales could equally be reaped by domestic enterprises irrespective of size. The observation that innovation into online sales could improve the performance of SMEs are well documented [7,8,26].…”
Section: Moderating Role Of Enterprise Size and Ownership Type On The...mentioning
confidence: 99%